Northward Spread of the Parrotfish Sparisoma cretense (Teleostei: Scaridae) in the Mediterranean Sea: An Update on Current Distribution with Two New Records from Sardinia - Giuseppe Esposito; Marino Prearo; Vasco Menconi; Davide Mugetti; Domenico Meloni; Mattia Tomasoni; Elisabetta Pizzul; Pierluigi Piras; Monia Renzi; Dario Gaspa; Paolo Pastorino (Journal of Marine Science and Engineering, 2021)
The parrotfish Sparisoma cretense, a marine species native to the eastern and southern coastal areas of the Mediterranean, has extended its distribution northward. Here, we provide an update on its distribution based on currently published data and two new records from the coastline of Sardinia, Italy (central-western Mediterranean). The survey methods were scuba diving and spearfishing: one specimen of S. cretense was caught along the Argentiera coastline (northwest Mediterranean) and the others were photographed in the Gulf of Orosei, Osalla Bay (central-eastern Mediterranean). A literature update, together with new records, documents the distribution of this species in the northernmost areas of the Mediterranean. Probably a result of global warming, the ongoing northward expansion of S. cretense highlights the need for sampling campaigns to obtain timely updates on population and distribution of this thermophilic species.